STRESS MANAGEMENT DURING PH.D. STUDIES: A SHARE OF REAL EXPERIENCES - Fadli Fizari Abu Hassan Asari; Azlina Mat Saad; Ar-Rayyan Fikri Fadli Fizari; Irhamna Fikri Fadli Fizari; Azlina Zid; Salwani Affandi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Effective and proficient stress management during the duration of a Ph.D. programme is critical for all Ph.D. students. This is done to ensure the emotional well-being of Ph.D students. Despite confronting a variety of hurdles and tests throughout the course of study, academic achievement remained consistently excellent. Travelling, cooking, reading, watching films, and gardening are just a few of the stress-relieving activities that are commonly mentioned on social media platforms like Facebook and blogs. However, we have chosen a unique technique, called play therapy, as our stress management therapy modality. Toys such as robots (Transformers), miniature car models (Hotwheels), blocks (LEGO/Kre-O), weapons and arrows (NERF), small train models (Thomas & Friends), and board games (Monopoly/Scrabble) were among our therapeutic goods during our Ph.D studies. The act of going to the store to buy new toys, the joy of finding a good deal on something we've been eyeing for a long, and the "hunt" for our all-time favourite toy are all components of this activity's therapeutic significance for us. As a result, the benefits of the toy treatment are felt not only by us but also by our children. Consequently, we are not the only ones who are experience it. We have taken toy collection treatment to an altogether new level. Whereas, as a family, we were able to successfully capture many medals, including gold medals, in international innovation competitions by leveraging our interest in collecting these toys. In addition, we presented papers on various elements of toy design at a number of international conferences. It is our honest hope that being able to speak and share our actual experiences of coping with stress while working on our Ph.D. can, to some extent, energise the sharing of many therapies that are already available for stress management.